Improvement of Inflammation through Antioxidant Pathway of Gardeniae Fructus 50% EtOH Extract (GE) from Acute Reflux Esophagitis Rats. (25th February 2020) - Kim, Soo Hyun; Shin, Mi-Rae; Lee, Ah Reum; Seo, Bu-Il; Park, Hae-Jin; Roh, Seong-Soo
Abstract : Gardeniae Fructus 50% EtOH extract (GE) is a traditional herb that has been used to treat a variety of diseases. In this study, we investigate the antioxidant, anti-inflammatory, and antiapoptotic properties of GE on acute reflux-induced esophagitis (RE) model in rats. 2, 2′-Azino-bis (3-ethylbenzothiazolin-6-sulfonic acid) (ABTS) and 2, 2-diphenyl-1-picrylhydrazyl (DPPH) radical scavenging assays were performed to determine the antioxidant activity of GE. GE was given orally at 50 and 100 mg/kg body weight 1h 30 min prior to RE induction. And its effect was assessed in comparison with RE control and normal groups. The administration of the extract of the GE showed remarkable protection of mucosal damage in esophageal tissue, and the histologic observation showed that the gastric lesion was improved. Increased reactive oxygen species (ROS) levels in the serum were diminished by GE treatment. The antioxidative biomarkers including nuclear factor-erythroid 2-related factor 2 (Nrf-2), heme oxygenase-1 (HO-1), superoxide dismutase (SOD), catalase, and glutathione peroxidase (GPX) were significantly increased. GE administration significantly reduced the inflammatory protein expression through MAPK-related signaling pathways and the nuclear factor-kappa B (NF- κ B) pathway. These results suggest that GE protects the esophagus mucosal membrane by attenuating oxidative stress and inflammatory response under reflux esophagitis condition through the antioxidant pathway. Therefore, it is suggested that GE may be a potential remedy for the treatment of reflux esophagitis.